Histopathological Analysis of Hysterectomy Specimens at a Tertiary Level Hospital of Nepal - Bhandari, Anita; Bagale, Bishow Bandhu (Journal of Bharatpur Hospital, 2025)
Background Hysterectomy is among the most frequently performed surgical procedures in tertiary care hospitals in Nepal. A variety of pathological conditions affecting cervix, endometrium, and myometrium often present with symptoms such as pelvic pain, abnormal bleeding, and infertility. The objective of this study is to determine the prevalence of uterine diseases leading to hysterectomy among patients at Bharatpur Hospital thereby providing valuable insights for accurate diagnosis and informed clinical management. Methods A cross-sectional study was conducted including 171 uterine specimens from patients who underwent hysterectomy between 1st April 2023 to 31st March 2024 at Bharatpur hospital, Chitwan, Nepal. Specimens were processed using standard histopathological techniques, including grossing, fixation in 10% formalin, section cutting with microtome and Hematoxylin & Eosin staining. Data was entered and analyzed using Microsoft Excel and Stata/BE version 18.0. Results Among the total 171 uterine specimens, the mean±SD of age was 48 ± 7.8 years. The minimum age was 30 years while maximum age was 74 years. Among them 148 (86.5%) underwent transabdominal hysterectomy, while 23 (13.5%) underwent vaginal hysterectomy. Chronic cervicitis was the most common cervical finding observed in 114 females (66.7%). Proliferative endometrium was the predominant endometrial finding observed in 97 females (56.7%). Leiomyoma was most frequently observed myometrial finding evident in 101 females (59.1%). Conclusions Chronic cervicitis, either in isolation or accompanied by other changes, was the most common histopathological finding in this study. These results underscore the importance of routine histopathological examination of hysterectomy specimens to ensure accurate diagnosis and appropriate management of underlying uterine conditions.